The electronic health record and primary health care in Greece: The case of local health units - Periklis, Rompolas; Masouras, Panicos; Avgousti, Sotiris; Charalambous, Andreas (My University, 2023)
The field of health today, influenced by technological developments, is in a dynamic stage of total transition from the handwritten file to the Electronic Health Record. In Greece, especially for Primary Health Care, although the efforts have been timeless and in some cases fragmentary, since 2017 the introduction of the Electronic Health Record in the newly established Local Health Units (ΤΟΜΥ) has been a technological innovation. Despite the shortcomings regarding the specialization of users, the interconnection of information with hospital units, as well as software compatibility problems, the capabilities it provides are the framework for continuous and quality health care that will be evidenced at the primary level, but will be disseminated to other levels of care. The primary goal should be to develop a national system with an emphasis on interoperability and equal access to the Electronic Health Record and other health professionals such as nurses, in order to provide a holistic health care framework. And it is an event that can be the focus of current and future e-health policies driven by health professionals as users of the Electronic Health Record.
Keywords: Electronic health record; E-health policies